Shakedown and collapse of elastic-plastic structures under variable and cyclic loads - Chinh, Pham Duc (Vietnam Journal of Mechanics, 2008)
The paper presents an introduction to the results obtained mainly by the author in shakedown analysis of elastic plastic structures, with the shakedown theorems for elastic plastic kinematic hardening materials playing the central role. Some illustrative examples of application are given